Legal Protection of the Parking Attendants for the Issuance of the Assignment Letter from the Transportation Department of Communication and Informatics Related to Employment Rights and Obligations in Bengkulu City - Ekke Widoto Khahar; Amancik Amancik; Amirizal Amirizal (Universitas Bengkulu, 2022)
Assignment Letter (SPT) is issued to the parking attendants after they meet the requirements set by Dishubkominfo (the Transportation Department of Communication and Informatics). The SPT contains only the duties and obligations of a parking attendant ordered by Dishubkominfo. The position of Dishubkominfo is higher, which is as the task provider for the parking attendant. Although these parking attendants play a role in Bengkulu City, they do not get protection. This could be seen in the SPT between Dishubkominfo and the parking attendants, which does not regulate protection for parking attendants at all. Thus, there is no legal certainty or protection for the parking attendants. The problems in this research were: What was the legal aspect of the position of the assignment letter from the Transportation Department of Communication and Informatics to the parking attendants in labor law in Bengkulu City? And what was the form of legal protection for parking attendants in the assignment letter from the Transportation Department of Communication and Informatics of Bengkulu City? The type of research used in this research was empirical juridical research. The results of this research were: Parking management in terms of collecting parking fees on the side of public roads in Bengkulu City was legally the duty and authority of Dishubkominfo. In its implementation, to collect parking fees, Dishubkominfo of Bengkulu City assigned the parking attendants based on the assignment letter (SPT). Legally, both parties have an employer and worker relationship as regulated in the Labour Laws where both parties have their respective rights and responsibilities. Thus, both parties also apply the provisions relating to Employment as regulated in the Labour Laws even though this is not regulated in the assignment letter (SPT) issued by Dishubkominfo of Bengkulu City. Legal protection of the parking attendants' rights relating to working hours, rest periods, occupational safety and health, wages, and social security has not been obtained by the parking attendants as it should have been determined by the Labour Laws and the Law on Social Security.